2010
DOI: 10.1002/humu.21313
|View full text |Cite
|
Sign up to set email alerts
|

MUT-TP53 2.0: a novel versatile matrix for statistical analysis of TP53 mutations in human cancera

Abstract: Analysis of the literature reporting p53 mutations shows that 8% of report display typographical mistakes with a notable increase in recent years. These errors are sometimes isolated, but in some cases, they concern several or even all mutations described in a single article. Furthermore, some works report unusual profile of p53 mutations whose accuracy is difficult to assess. To handle these problems we have developed MUT-TP53 2.0, an accurate and powerful tool that will automatically handle p53 mutations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Approximately 80% of these missense mutations were projected to generate an inactive or partially inactive p53 protein (Fig. 3B) as determined by TP53-MUT 2.00, an online tool that predicts the biological activity of known TP53 mutations (24). In addition, missense mutations were enriched in the 9 most commonly mutated "hotspot" TP53 codons (175, 179, 195, 220, 237, 245, 248, 273, and 282) in ovarian carcinomas according to the IARC database (21,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80% of these missense mutations were projected to generate an inactive or partially inactive p53 protein (Fig. 3B) as determined by TP53-MUT 2.00, an online tool that predicts the biological activity of known TP53 mutations (24). In addition, missense mutations were enriched in the 9 most commonly mutated "hotspot" TP53 codons (175, 179, 195, 220, 237, 245, 248, 273, and 282) in ovarian carcinomas according to the IARC database (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…All missense biological background mutations were evaluated by MUT-TP53 2.00 (24). Using functional and statistical information derived from the UMD (Universal Mutation Database) p53 database, this matrix assesses the likely biological activity of each mutation and categorizes them as one of the following: "inactive," "partially active," or "no significant loss of activity.…”
Section: Methodsmentioning
confidence: 99%
“…13) and obtained using the MUT-TP53 2.0 Excel spreadsheet tool (22), which was also used to perform comparison of our dataset with previous publications using the mean and 95% confidence interval (CI) of p53 activity as measured by transactivation with the WAF1 promoter. In the validation cohort, the mean of our study was À1.27 for EGFR-wt and À1.34 for EGFR-mut, compared with À1.26 and À1.29 in the two comprehensive NSCLC studies reported in the tool.…”
Section: Analysis Of Tp53 Mutationsmentioning
confidence: 99%
“…25,26 The frequency (number of reported mutations in all cancers) and predicted TP53 residual activity was retrieved from the 2007_R1 release of the UMD_TP53 Mutation database (http://p53.free.fr). 27 Known polymorphisms in the TP53 gene were treated as being TP53 wild type.…”
Section: Analysis Of Tp53 Mutationsmentioning
confidence: 99%